2014
DOI: 10.1093/jac/dku441
|View full text |Cite
|
Sign up to set email alerts
|

Imaging the distribution of polymyxins in the kidney

Abstract: The observed accumulation of polymyxin B within proximal tubular cells is consistent with the extensive renal reabsorption of polymyxins and the likely cause of the associated nephrotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
70
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(73 citation statements)
references
References 16 publications
2
70
0
1
Order By: Relevance
“…Our group also reported that polymyxin B was preferentially accumulated in rat kidneys with a prolonged residence time (23). In a mouse model, polymyxin B was found to be substantially accumulated in the renal proximal tubular cells (24), which was previously observed to be the primary renal injury site in a rat model (25). Furthermore, polymyxin B recovery from urine was reported to be very low in several studies.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Our group also reported that polymyxin B was preferentially accumulated in rat kidneys with a prolonged residence time (23). In a mouse model, polymyxin B was found to be substantially accumulated in the renal proximal tubular cells (24), which was previously observed to be the primary renal injury site in a rat model (25). Furthermore, polymyxin B recovery from urine was reported to be very low in several studies.…”
Section: Discussionmentioning
confidence: 53%
“…Second, Yun et al provided circumstantial evidence linking polymyxin B distribution to the site of renal injury (24). We have previously shown histological evidence that the polymyxin B-induced injury was confined mainly to the proximal tubular cells of the rat kidneys (25).…”
Section: Discussionmentioning
confidence: 88%
“…2A). Hence, the accumulation of polymyxin B in both A549 and HK-2 cells was determined (25) by using an anti-polymyxin B MAb. Interestingly, substantially less accumulation of polymyxin B was observed in A549 cells than in HK-2 cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Because the ratios in these studies were for kidney homogenate (27,28), they would underestimate the concentration in the region of the greatest polymyxin accumulation. Immunostaining studies of sections of rodent kidneys from animals treated with PMB have shown that accumulation occurs predominantly in the renal cortex, primarily within proximal tubular cells (28,29). A synchrotron X-ray fluorescence microscopy study revealed that the concentration of a polymyxin analog in single rat (NRK-52E) and human (HK-2) kidney tubular cells in culture was several thousandfold higher than the extracellular concentration (30).…”
Section: To What Extent Do Polymyxins Accumulate In the Kidney And Whmentioning
confidence: 99%